Validity and Reliability of Indonesian Version of Diabetes Quality of Life Brief Clinical Inventory in Patients with Type 2 Diabetes at Primary Care - Azmiardi, Akhmad; Febrinasari, Ratih Puspita (MAGNA MEDIKA Berkala Ilmiah Kedokteran dan Kesehatan, 2025)
Background:  Type 2 diabetes (T2DM) has a significant impact on patients' quality of life (QoL), including physical, psychological, social, and economic aspects. However, a culturally and linguistically adapted Diabetes Quality of Life Brief Clinical Inventory (DQoL-BCI) for Indonesian patients remains limited. A validated Indonesian version of this instrument is necessary to ensure accurate assessment and effective interventions for diabetes management.Objective: This study aimed to assess the validity and reliability of the Indonesian version of the Diabetes Quality of Life Brief Clinical Inventory (DQoL-BCI) among patients with T2DM in primary care.Methods: A cross-sectional study was conducted among 30 T2DM patients at a primary health care center in Singkawang City, West Borneo, Indonesia. Data were collected through interviews. The DQoL-BCI, a 15-item questionnaire, was used to measure QoL, with responses rated on a 5-point Likert scale. Construct validity and internal consistency were assessed using Pearson’s r and Cronbach’s alpha.Results: All items showed Pearson’s r values greater than 0.361, indicating an adequate correlation with the overall scale and thus validating the items. The highest Pearson’s r values were for satisfaction with the time to determine sugar levels (0.688) and sex life (0.680). The Cronbach’s alpha coefficient for all items was 0.887, exceeding the minimum requirement of 0.70, demonstrating excellent internal consistency.Conclusion: The Indonesian version of the DQoL-BCI is a valid and reliable instrument for measuring the QoL in individuals with T2DM in primary care settings.